Postinspiratory and preBötzinger complexes contribute to respiratory-sympathetic coupling in mice before and after chronic intermittent hypoxia - Karlen-Amarante, Marlusa; Glovak, Zachary T.; Huff, Alyssa; Oliveira, Luiz M.; Ramirez, Jan-Marino (Frontiers in Neuroscience, 2024)
The sympathetic nervous system modulates arterial blood pressure. Individuals with obstructive sleep apnea (OSA) experience numerous nightly hypoxic episodes and exhibit elevated sympathetic activity to the cardiovascular system leading to hypertension. This suggests that OSA disrupts normal respiratory-sympathetic coupling. This study investigates the role of the postinspiratory complex (PiCo) and preBötzinger complex (preBötC) in respiratory-sympathetic coupling under control conditions and following exposure to chronic intermittent hypoxia (CIH) for 21 days (5% O2–80 bouts/day). The surface of the ventral brainstem was exposed in urethane (1.5 g/kg) anesthetized, spontaneously breathing adult mice. Cholinergic (ChAT), glutamatergic (Vglut2), and neurons that co-express ChAT and Vglut2 at PiCo, as well as Dbx1 and Vglut2 neurons at preBötC, were optogenetically stimulated while recording activity from the diaphragm (DIA), vagus nerve (cVN), and cervical sympathetic nerve (cSN). Following CIH exposure, baseline cSN activity increased, breathing frequency increased, and expiratory time decreased. In control mice, stimulating PiCo specific cholinergic-glutamatergic neurons caused a sympathetic burst during all phases of the respiratory cycle, whereas optogenetic activation of cholinergic-glutamatergic PiCo neurons in CIH mice increased sympathetic activity only during postinspiration and late expiration. Stimulation of glutamatergic PiCo neurons increased cSN activity during the postinspiratory phase in control and CIH mice. Optogenetic stimulation of ChAT containing neurons in the PiCo area did not affect sympathetic activity under control or CIH conditions. Stimulating Dbx1 or Vglut2 neurons in preBötC evoked an inspiration and a concomitant cSN burst under control and CIH conditions. Taken together, these results suggest that PiCo and preBötC contribute to respiratory-sympathetic coupling, which is altered by CIH, and may contribute to the hypertension observed in patients with OSA.